1992
DOI: 10.1148/radiology.182.1.1727284
|View full text |Cite
|
Sign up to set email alerts
|

Rapid destructive osteoarthritis: clinical, radiographic, and pathologic features.

Abstract: Twenty-seven cases of an unusual, poorly recognized destructive hip arthropathy with radiographic findings of rapid severe joint destruction are presented. Radiographic findings mimicked those of other disorders such as septic arthritis, rheumatoid and seronegative arthritis, primary osteonecrosis with secondary osteoarthritis, or neuropathic osteoarthropathy, but none of the patients had clinical, pathologic, or laboratory evidence of these entities. All patients underwent hip arthroplasty, and osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 0 publications
6
75
1
2
Order By: Relevance
“…We found that the mean serum MMP-3 level in women with rapidly destructive hip OA was 100 Ϯ 63 ng/ml, a value 2-3 times higher than that in women with ordinary hip OA. Synovial fibroblast adhesion to articular cartilage is commonly observed in RA (22) as well as in rapidly destructive hip OA (23). Our finding that synthesis of MMP-3 by synovium was significantly higher in patients with rapidly destructive hip OA than in those with OA is consistent with the findings of previous semiquantitative studies (7,8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the mean serum MMP-3 level in women with rapidly destructive hip OA was 100 Ϯ 63 ng/ml, a value 2-3 times higher than that in women with ordinary hip OA. Synovial fibroblast adhesion to articular cartilage is commonly observed in RA (22) as well as in rapidly destructive hip OA (23). Our finding that synthesis of MMP-3 by synovium was significantly higher in patients with rapidly destructive hip OA than in those with OA is consistent with the findings of previous semiquantitative studies (7,8).…”
Section: Discussionsupporting
confidence: 92%
“…MMP-9 can also be produced by activated osteoclasts (34). A number of osteoclasts in rapidly destructive hip OA, which are one source of MMP-9, have been observed around necrotic bone in subchondral areas (23,24). A recent study also demonstrated that MMP-9 was strongly expressed in the subchondral region in RA patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic findings in this disease can mimic those of other disorders, such as septic arthritis, rheumatoid and seronegative arthritis and primary osteonecrosis with secondary OA [21]. However, none of our patients had clinical, pathologic or laboratory evidence of these entities.…”
Section: Discussionmentioning
confidence: 64%
“…However, none of our patients had clinical, pathologic or laboratory evidence of these entities. Repeated minor trauma with subsequent stress fractures, excessive locomotor activity and femoral-head hypoxia due to atherosclerotic vasculopathy have been proposed as predisposing factors [21]. Yet these factors were only present in two of our patients with a rapid progression of the disease, rendering a causative explanation unlikely.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation